Investigation of the Mechanical Properties and the Corrosion Behaviour of Low Alloyed Magnesium ? Calcium ?Alloys for use as Absorbable Biomaterial in the Implant Technique - Th. Hassel (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
The application of magnesium as an absorbable biomaterial demanded the consideration of the alloy composition, the mechanical properties and the corrosion a special adapted material development in terms of the human biological system. Magnesium for technical applications mostly comprised alloying elements up to 10 wt%. Thereby often metals (e.g. rare earth and aluminum) with high toxic potentials are used to optimize the mechanical properties. To minimize toxic reactions during the degradation of a absorbable magnesium alloy, the Mg-Ca system is being selected and investigated because both elements belong to the mineral nutrients. Rods and small tubes are produced by extrusion of gravity die casting billets (Ca-content 0.4 to 4.0wt%). The positive grain fining influence of calcium and its improvement of the corrosion behavior are additional advantages. The microstructure, the mechanical properties and the corrosion attitude are investigated. The results show that an optimal composition of micro alloyed Mg-Ca and ideally processing parameters lead to 16% strain and a tensile strength up to 185MPa. Electrochemical investigations and measurements of the hydrogen production demonstrate the influence of the Ca-content to the corrosion behavior of the investigated alloys.